An assessment of trade in gibbons and orang-utans in Sumatra, Indonesia - Nijman, Vincent (A Traffic Southeast Asia report, 2009)
This report presents an assessment of the trade in gibbons and orang-utans in Sumatra, Indonesia, including the islands off Sumatra?s west coast (most notably, the Mentawai Islands). Until recently Sumatra and its off-lying islands harboured one of the largest expanses of lowland evergreen rainforest in Southeast Asia. Most of the lowland forests are gone and the forest that remains is largely in the hills and mountains, running along the western part of the island, with the largest expanse of forests being in the Leuser Ecosystem, and adjacent Ulu Masen forest to the north. Commercial timber extraction, small-scale logging (legal and illegal), conversion of forest to palm oil or wood-pulp plantations, and forest fires ? along with the concurrent increase in access to formerly remote areas ? are increasingly threatening the integrity of the remaining forests, thus putting the survival of its inhabitants at stake.